2022
DOI: 10.1038/s41467-022-32158-7
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol sulfate alleviates ulcerative colitis by promoting cholesterol biosynthesis in colonic epithelial cells

Abstract: Cholesterol sulfate, produced by hydroxysteroid sulfotransferase 2B1 (SULT2B1), is highly abundant in the intestine. Herein, we study the functional role and underlying intestinal epithelial repair mechanisms of cholesterol sulfate in ulcerative colitis. The levels of cholesterol and cholesterol sulfate, as well as the expression of Sult2b1 and genes involved in cholesterol biosynthesis, are significantly higher in inflamed tissues from patients with ulcerative colitis than in intestinal mucosa from healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…[ 79 , 80 ] We found that the classical metabolite of squamous cell carcinoma, cholesterol sulfate ( m/z 465.3044), exhibited a specific accumulation and distribution in the malignant epithelial region of OSF‐derived OSCC, which may be associated with tumor cell differentiation and the inhibition of immune cell infiltration and activation. [ 81 , 82 , 83 ] Phospholipids are important components of the cellular membrane system, and phospholipid metabolism in tumor cells has attracted attention as a potential target for cancer therapy. [ 84 ] Our results revealed that phosphatidyl ethanolamine (PE (28:1), m/z 634.4442) had a relatively higher abundance in the Adjacent Epithelium and ISC regions, while phosphatidyl choline (PC (38:7), m/z 804.5539) and phosphatidyl serine (PS (38:4), m/z 810.5292) were remarkably enriched in the Stroma and OSF regions (Figure S8 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 79 , 80 ] We found that the classical metabolite of squamous cell carcinoma, cholesterol sulfate ( m/z 465.3044), exhibited a specific accumulation and distribution in the malignant epithelial region of OSF‐derived OSCC, which may be associated with tumor cell differentiation and the inhibition of immune cell infiltration and activation. [ 81 , 82 , 83 ] Phospholipids are important components of the cellular membrane system, and phospholipid metabolism in tumor cells has attracted attention as a potential target for cancer therapy. [ 84 ] Our results revealed that phosphatidyl ethanolamine (PE (28:1), m/z 634.4442) had a relatively higher abundance in the Adjacent Epithelium and ISC regions, while phosphatidyl choline (PC (38:7), m/z 804.5539) and phosphatidyl serine (PS (38:4), m/z 810.5292) were remarkably enriched in the Stroma and OSF regions (Figure S8 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Given the results of this study, we strongly recommend further in vitro (for example, thrombo-elastography) and in vivo (for example, animal models of venous and arterial thrombosis) investigation of CS to better understand its (patho-)physiological roles in coagulation and hemostasis which may intersect with the other reported biological effects of CS [ [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that IEC-specific Sult2b1 deletion mice (Sult2b1 f/f Villin-Cre mice) develop severe DSS-induced colitis, compared with the control Sult2b1 f/f mice (24). Although they suggested that CS alleviates gut inflammation by promoting cholesterol biosynthesis in IECs (24), the effect of CS on intestinal immune cells remains unexplored. DOCK2 is a Rac activator predominantly expressed in hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and mice, cholesterol sulfation is mediated primarily by the sulfotransferases SULT2B1b and, to a lesser extent, SULT2B1a, which are produced from the same gene, SULT2B1, through alternative splicing (22,23). Currently, CS has been implicated in many biological processes including sperm capacitation, platelet adhesion, blood clotting, cholesterol or leukotriene biosynthesis, and T-cell receptor signaling (21, 24,25). In addition, we have revealed that CS is an endogenous inhibitor of DOCK2 (26).…”
Section: Introductionmentioning
confidence: 99%